2017
DOI: 10.1038/s41598-017-02596-1
|View full text |Cite|
|
Sign up to set email alerts
|

White matter microstructural changes are related to cognitive dysfunction in essential tremor

Abstract: Diffusion tensor imaging (DTI) studies have detected white matter microstructural changes in essential tremor (ET). However, it is still unclear whether these changes are related to cognitive deficits, which have been described in ET patients. DTI-derived fractional anisotropy, mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity measures were compared between 23 ET patients and 23 age-, gender-, and education-matched healthy individuals, using whole-brain tract-based spatial statistics. Corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 52 publications
1
20
0
1
Order By: Relevance
“…To our knowledge, there is no study reported relationship of AD value with cognitive function in schizophrenia. The studies on patients with essential tremor showed positive correlation between the AD value and cognitive function (Julian et al, ; Bhalsing et al, ). Same as these previous studies on essential tremor, our SZ group showed significant relationship of increased AD with better attention scores, while AD value in the SZ group was significantly increased compared to the HC group.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there is no study reported relationship of AD value with cognitive function in schizophrenia. The studies on patients with essential tremor showed positive correlation between the AD value and cognitive function (Julian et al, ; Bhalsing et al, ). Same as these previous studies on essential tremor, our SZ group showed significant relationship of increased AD with better attention scores, while AD value in the SZ group was significantly increased compared to the HC group.…”
Section: Discussionmentioning
confidence: 99%
“…The posterior thalamic radiation is also related to cognition in some way. Previous researchers have revealed that posterior thalamic radiation damage was related to cognition in essential tremor ( 54 ) and may also be associated with intellectual performance ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though it is not impossible for memory deficits (or language and spatial deficits) to reflect the distal effects of cerebellar compromise on hippocampal, temporal and parietal regions respectively, such cognitive deficits might be explained more parsimoniously by direct deterioration of these regions, such as that which may occur early in the course of Alzheimer's disease [44][45][46]. Consistent with a neuropathological model of cognitive impairment in ET that extends beyond the cerebellum, diffusion tensor imaging (DTI) studies have shown that the integrity of white matter microstructure is compromised throughout the brain [47], resting state imaging has revealed altered functional connectivity throughout the cerebral cortex [48] [49], and structural MRI has shown smaller cerebral cortical gray matter volume [50]. In at least a subset of ET cases, therefore, there appears to be a neurodegenerative process occurring outside of the cerebellum at a higher rate than that which is seen in age matched controls [47,51].…”
Section: Nature and Neuroanatomic Substrates Of Cognitive Impairment mentioning
confidence: 99%